To Control Electrical MCBs using Hand Gesture Recognition - Goyal, sangeeta; Kumar, Dr. Bhupesh (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
There has been growing interest in development of new techniques and methods for Human-Computer Interaction (HCI). Gesture Recognition is one of the important areas of this technology. Gesture Recognition means interfacing with computer using motion of human body typically hand movements. As a Handicapped person cannot move very easily and quickly if there is a fire in house or he/she cannot switch off the Miniature Circuit Breaker (MCB) but the same task can be done easily with hand gesture recognition. In our proposed system electrical MCB can be controlled using hand gesture recognizer. To switch on/off the MCB, we need to provide hand based gesture as an input to system.